The Advantages of Sharia Value Added Business in Realizing the Sustainability of Traditional Enterprises in Gattareng Village - Sufiani Zahra; Muhammad Wahyuddin Abdullah; Supriadi; Mukhtar Lutfi; Amiruddin (LP2M IAIN Palopo, 2026)
This study aims to analyze the advantages of sharia value-added business in realizing the sustainability of traditional enterprises in Gattareng Village. This research employs a qualitative approach using a field study method involving traditional business actors, such as gogos sellers, banana sellers, and agricultural middlemen. The data were collected through observation, in-depth interviews, and documentation, and were then analyzed descriptively from the perspective of sharia value-added principles. The results of the study indicate that the implementation of sharia principles in traditional businesses not only generates economic value but also forms mental, social, and spiritual values that simultaneously strengthen business sustainability. Sharia value-added is manifested through honesty, fairness in pricing, transparency, social responsibility, and adherence to halal principles, which help build trust as a primary form of social capital. The integration of spiritual values, including the concept of Manunggaling Kawula Gusti, emphasizes that economic activities are understood as a form of devotion to God, giving rise to inner peace, blessings in business, and harmonious social relations. The business advantages obtained are multidimensional, encompassing financial profit, public trust, inner satisfaction, and the sustainability of business relationships. This study concludes that sharia value-added constitutes a holistic business paradigm and has the potential to serve as a foundation for the sustainability of traditional enterprises, particularly in rural areas, within the framework of a just, ethical, and sustainable Islamic economy.